Leveraging the Use of Social Media in Teaching Writing: A Qualitative Investigation among ESL Pre-Service Teachers - Rusli, Rusreena; Hashim, Harwati; Md Yunus, Melor; Zakaria, Nur Yasmin Khairani; Norman, Helmi (International Journal of Interactive Mobile Technologies (iJIM), 2019)
Advances of technology and innovation suggest new form and paths in language teaching. Social media use can be a great influence for English as a Second Language (ESL) students especially in writing competency. Despite of many positive reports that presented affordances in social media use, however, there are insufficient studies that investigate ESL trainee teachers’ perception on this matter. Therefore, this study aimed to investigate ESL pre-service teachers’ views upon leveraging the use of social media in teaching of writing focusing on the opportunities and challenges. This study employed qualitative methods where thirty-four ESL pre-service teachers from a public university were involved. Based on the findings, it can be concluded that ESL pre-service teachers perceived the use of social media in teaching writing can be of beneficial and similarly challenging. Opportunities stated by the participants include enhancement in collaborative learning, supporting students’ self-directed learning and simplify the teaching and learning processes. On the other hand, the challenges mentioned by the participants are that social media can be a source of distraction, deterioration in language and plagiarism. Thus, it is advisable that teachers play their roles responsibly in managing students’ activities online and also be equipped with technology skills to enhance the establishments of social media in ESL teaching of writing.